Reimagining Nabokov Pedagogies for the 21st Century - Karpukhin, Sara; Vergara, José (Amherst College Press, 2022)
In Reimagining Nabokov: Pedagogies for the 21st Century, eleven teachers of Vladimir Nabokov describe how and why they teach this notoriously difficult, even problematic, writer to the next generations of students. Contributors offer fresh perspectives and embrace emergent pedagogical methods, detailing how developments in technology, translation and archival studies, and new interpretative models have helped them to address urgent questions of power, authority, and identity. Practical and insightful, this volume features exciting methods through which to reimagine the literature classroom as one of shared agency between students, instructors, and the authors they read together. "It is both timely and refreshing to have an influx of teacher-scholars who engage Nabokov from a variety of perspectives... this volume does justice to the breadth of Nabokov's literary achievements, and it does so with both pedagogical creativity and scholarly integrity" • Dana Dragunoiu, Carleton University